Stylistic Analysis of Selected Primary School Nursery Rhymes and Implications on Pupils’ Reading Comprehension - OLAWE, Opeyemi Emmanuel (CV. Creative Tugu Pena, 2023)
This study carried out a stylistic analysis of primary school nursery rhymes and their implications on reading skills of pupils. The study utilized descriptive research design where five nursery rhymes were randomly selected from a nursery rhyme textbook. The selected nursery rhymes were based on the popularity of the rhymes among the primary school children. The data obtained from the study was analyzed stylistically using the levels of stylistic analysis which include graphology, phonology, lexical and syntactic levels. Findings demonstrate that all the words choice in nursery rhymes is deliberately simpler so that the readers may understand the theme and the message of the rhymes. The rhymes are often based on simple shorter sentences, although long sentences can occur as well. Based on the age of the children, information is presented in a simple manner. The stings of sentences are not too long for the children to comprehend and the phrases and sentences are logically linked together to create a cohesive and perfect rhythm. The occurrence of rhyming especially end rhymes facilitate children’s learning faculty as they are reading the rhymes through the repetition of similar sounding words at the ending of a verse or line. This creates a mnemonic situation in which it is easier for the readers to memorise their reading through smooth and pleasurable reading experience.Keywords: Linguistic Resources, Nursery Rhymes, Primary School, Reading Comprehension